Social transformation of Indian tribal community : unlocking the potential by healthcare - Ravichandran, N., (SAGE Knowledge. Cases., 2017)
The case documents the evolution (2011-2016) of Tejas Eye Hospital (TEH) promoted by a not-for profit trust located in Mandvi, Surat district, close to a tribal community settlement in Gujarat state, India.In five years, the trust-based hospital has evolved as a vibrant community hospital. The trusts activities include: medical education, prevention of ophthalmological diseases by screening in camps, treatment, and need based rehabilitation and addressing the primary, and indirect healthcare needs of the community. However, in order to continue serving the medical needs of the community and expand, the board of trustees need to strengthen and refine its operating business model of the hospital.